Computer-Aided Design of Multi-Agent Cyber-Physical Systems - Sini, J.; Violante, M.; Dessi, R. (Proceedings (IEEE International Conference on Emerging Technologies and Factory Automation), 2018)
This paper presents a methodology to aid the development of multi-agent cyber-physical systems. The software architecture is structured in a multi-layer fashion, distributed on different devices (agents), making its design very challenging. A methodology is thus needed to meet the performance goal of such a system. The proposed methodology relies on Model-Based Software Design techniques, and on the Model/Software/Hardware-In-The-Loop (MIL, SIL, HIL) simulations. In particular, the HIL verification technique, which is widely adopted in the automotive and avionic industry also in the early development phases as a Computer-Aided Design tool, is the core tool of the real-time performances assessment verification. To speed-up the development process, and to obtain a toolchain coherent with the proposed approach, the adoption of a Model-Based Software Design methodology represents an optimal solution. Within those assumptions, we propose a benchmark of the methodology, applied on a customized multiagent system. The aim is to prove that the proposed method is able to achieve and verify a set of real-time requirements on the system behavior.